2022
DOI: 10.1038/s41598-022-10207-x
|View full text |Cite
|
Sign up to set email alerts
|

Latent state-trait structure of BPRS subscales in clinical high-risk state and first episode psychosis

Abstract: To investigate the longitudinal latent state-trait structure of the different dimensions of psychosis symptoms in clinical high-risk state (CHRS) and first episode psychosis (FEP) individuals over a one year time-span. This paper examines if the symptom clusters Positive Symptoms, Negative Symptoms, Affectivity, Resistance, Activation, and Excitement according to the Brief Psychiatric Rating Scale (BPRS) differ in their trait and state characters in 196 CHRS and 131 FEP individuals. Statistical analysis was pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(54 reference statements)
2
0
0
Order By: Relevance
“…Increased levels of OA were also associated with the severity of cognitive deficits in the FES group (rho = −0.60), although this did not survive multiple comparison corrections. Since NA is abundant in brain white matter and plays a crucial role in myelin maturation and integrity ( 17 ), our results may be partly in line with neuroimaging evidence that abnormalities in brain connectivity contribute to trait characteristics of psychosis, such as negative symptomatology ( 61 ) and cognitive deficits ( 62 ) in ARMS ( 63 ) and schizophrenia ( 64 ). Previous studies on FAs in ARMS and FES have also demonstrated an increased NA level ( 18 , 20 ) and its relationship with symptom severity ( 18 , 28 , 31 ).…”
Section: Discussionsupporting
confidence: 85%
“…Increased levels of OA were also associated with the severity of cognitive deficits in the FES group (rho = −0.60), although this did not survive multiple comparison corrections. Since NA is abundant in brain white matter and plays a crucial role in myelin maturation and integrity ( 17 ), our results may be partly in line with neuroimaging evidence that abnormalities in brain connectivity contribute to trait characteristics of psychosis, such as negative symptomatology ( 61 ) and cognitive deficits ( 62 ) in ARMS ( 63 ) and schizophrenia ( 64 ). Previous studies on FAs in ARMS and FES have also demonstrated an increased NA level ( 18 , 20 ) and its relationship with symptom severity ( 18 , 28 , 31 ).…”
Section: Discussionsupporting
confidence: 85%
“…NA is an essential molecule for the growth and maintenance of integrity in the white matter and peripheral nervous tissue enriched by sphingomyelin ( 63 ) and is suggested to be related to psychiatric disorders ( 64 ). Our results may be partly in line with the neuroimaging evidence that abnormalities in brain connectivity contribute to the trait characteristics of schizophrenia ( 65 ), such as negative symptomatology ( 66 ) and cognitive deficits ( 67 ). Because the impaired integrity of white matter is also reported in depression ( 68 70 ), it may be possible that NA abnormalities commonly contribute to the pathophysiology of both schizophrenia and depression.…”
Section: Discussionsupporting
confidence: 88%